Interactive Physical Design Tuning - Bruno, Nicolas; Chaudhuri, Surajit (ICDE, 2010)
In the last decade, automated physical design tuning became a relevant area of research. The process of tuning a workload became more flexible but also more complex, and getting the best design upfront became difficult. We propose a paradigm shift for physical design tuning, in which sessions are highly interactive, allowing DBAs to quickly try different options, identify problems, and obtain physical designs in an agile manner.